AN INTEGRATED SUPPLY CHAIN WITH UNCERTAIN DEMAND AND RANDOM DEFECT RATE UNDER CARBON CAP-AND-TRADE POLICY - Ghosh, Arindam; Jha, J. K.; Sarmah, S. P. (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
In this paper, we study a vendor-buyer integrated supply chain with uncertain demand and random defect rate under carbon cap-and-trade policy. We assume that the lot sent by the vendor to the buyer in each shipment contains a random fraction of defective item, and a fraction of defective items can be repaired. The defective items get screened at the buyer and sent back to the vendor, and the vendor sorts out the repairable items. At the end of each production cycle, the accumulated repairable items at the vendor are repaired in a single lot. We have taken into account the carbon emissions from all the major sources, i.e. production, inventory, transportation, repairing, and scrapping. Shortages at the buyer are partially backordered. A mathematical model is formulated to minimize the total expected cost of the supply chain by optimizing the order quantity, reorder point, and the number of shipments between the vendor and buyer under carbon cap-and-trade policy. An algorithm is proposed to solve the model. A numerical example and sensitivity analysis are presented to get some managerial insights.